Wellbeing in the Irish Junior Cycle: the potential of Religious Education. Issue 4 (2nd October 2019) - Meehan, Amalee
Abstract : Wellbeing is central to the new Junior Cycle (lower secondary education) in Ireland as a principle and curricular area. This paper argues that while it should never be the case that the rights of parents or their children regarding Religious Education are compromised, Religious Education can make a real and positive contribution to wellbeing in the Junior Cycle. The paper begins by reviewing two recent international longitudinal studies to demonstrate the strong positive correlation between religion and wellbeing. It goes on to highlight the potential of Religious Education in helping schools to fulfil the Junior Cycle wellbeing requirements. It concludes that as a legitimate source of wellbeing, Religious Education with sound content and pedagogy, well taught by qualified and supported teachers, can be an integral part of a Junior Cycle programme.